Spatiotemporal Regulation of STING Activity by Linear Ubiquitination Governs Antiviral Immunity - Yong Zhang; Yesheng Fu; Lihua Qiang; Mengyuan Zhao; Zhe Lu; Zhuo Zhao; Guoping Chen; Zehui Lei; Qiyao Chai; Pupu Ge; Bingxi Li; Jing Wang; et al. (Advanced Science)
Abstract The cyclic GMP‐AMP synthase (cGAS)‐stimulator of interferon gene protein (STING) signaling plays a critical role in innate immunity and must be tightly regulated to maintain immune homeostasis, but the mechanism underlying the spatiotemporal regulation of this pathway remains largely elusive. Here, it is shown that during DNA viral infection, the linear ubiquitin chain assembly complex (LUBAC) and ovarian tumor deubiquitinase with linear linkage specificity (OTULIN) reversibly catalyze the linear ubiquitination of STING. At the early stage of the infection, LUBAC promotes STING linear ubiquitination to drive its trafficking from the endoplasmic reticulum (ER) to the Golgi apparatus through binding to the Sec24b subunit of the coat protein complex II (COPII) complex. Later on, OTULIN is recruited to TANK1 binding kinase 1 (TBK1)‐phosphorylated STING and removes its linear ubiquitin chains, thus preventing excessive antiviral immune responses. Together, the study uncovers a linear ubiquitination‐governed spatiotemporal regulatory mechanism that fine‐tunes STING‐driven antiviral immunity.